INFLUENCE OF THERMAL TREATMENT ON THE ELECTROPHYSICAL PROPERTIES OF SILICON STRUCTURES WITH RARE-EARTH ELEMENTS - Yusupov, Oralbay Naurizbaevich (SCIENCE and SOCIETY, 2026)
The article to study the mechanisms of electrophysical processes, deep level formation, and interaction with technological impurities (oxygen and carbon) occurring during high-temperature heat treatment in silicon monocrystals doped with rare earth elements such as samarium, gadolinium, and itterbium. Samples grown by the Chohralski method and doped by diffusion were studied using neutron activation analysis, IR spectroscopy, isothermal capacitance relaxation, and four-probe methods.
Keywords: semiconductor; silicon; n-type silicon; the influence of thermal effects; electrophysical properties; structures with Sm, Gd, and Yb during growth; silicon during heat treatments